Dyslipidemia and the Prevalence of Hypertension: A Cross-Sectional Study Based on Chinese Adults Without Type 2 Diabetes Mellitus - Cheng, Wenke; Zhuang, Jingqi; Chen, Siwei (Frontiers in Cardiovascular Medicine, 2022)
Background: In clinical practice, it is frequently observed that patients with hypertension often coexist with dyslipidemia. However, studies on atherosclerotic indices and the incidence of hypertension are limited. The purpose of this study was to assess the relationship between atherosclerotic indices and the incidence of hypertension. Methods: A cross-sectional study was conducted based on 117,056 adults in 11 Chinese cities from 2010 to 2016. Eight atherosclerosis indices namely the atherogenic coefficient (AC), Castelli’s risk index I (CRI-I) and II (CRI-II), the atherogenic index of plasma (AIP), the cholesterol index, the lipoprotein combined index (LCI), non-HDL-C and TG/HDL-C were analyzed in this study. Two groups of continuous variables were measured using the Man-Whitney test, and categorical variables were analyzed using the Chi-square test. Furthermore, Spearman correlation analysis and multivariate logistic regression analyses were performed to assess the relationship between atherosclerotic indices and blood pressure levels, and the incidence of hypertension, respectively. The results were expressed as the odds ratio (OR) and their corresponding 95% confidence intervals (CIs). Results: Atherosclerosis indices were increased in the hypertensive population compared to those in the normotensive population. Meanwhile, systolic blood pressure (SBP) and diastolic blood pressure (DBP) were linearly and positively correlated with atherosclerotic indices. In addition, multivariate logistic regression analysis showed that the cholesterol index and non-HDL-C were observed to be positively associated with the incidence of hypertension (p for trend＜0.05). Moreover, the incidence of hypertension increased by 3.7% (OR: 1.037; 1.009-1.06) and 6.1% (OR: 1.06; 1.033-1.091), respectively, as per SD increase in the cholesterol index and non-HDL-C. ROC analysis demonstrated that the cholesterol index and non-HDL-C have a good predictive value for the incidence of hypertension in women, with AUC of 0.659 and 0.684 and cut-off values of 47.94 and 134.34 mg/dl, accordingly. Conclusions: Atherosclerotic indices were significantly increased in hypertensive populations compared with those in normotensive populations, regardless of hypertension levels. Meanwhile, SBP and DBP were linearly and positively related to atherosclerotic indices. Besides, the cholesterol index and non-HDL-C were independent risk factors for the incidence of hypertension, and they could be adopted for effectively predicting the incidence of hypertension in women.